Modular Programming Languages 7th Joint Modular Languages Conference, JMLC 2006, Oxford, UK, September 13-15, 2006, Proceedings - Lightfoot, David; Szyperski, Clemens (Theoretical Computer Science and General Issues, 2006)
On behalf of the Steering Committee we are pleased to present the proceedings of the 2006 Joint Modular Languages Conference (JMLC), organized by Oxford Brookes University, Oxford, UK and held at Jesus College, Oxford. The mission of JMLC is to explore the concepts of well-structured programming languages and software and those of teaching good design and programming style. JMLC 2006 was the seventh in a series of successful conferences with themes including the construction of large and distributed software systems, and software en- neering aspects in new and dynamic application areas. We were fortunate to have a dedicated Program Committee comprising 41 internationally recognized researchers and industrial practitioners. We received 36 submissions and each paper was reviewed by at least three Program C- mittee members (four for papers with an author on the Program Committee). The entire reviewing process was supported by the OpenConf system. In total, 23 submissions were accepted along with two invited papers and are included in this proceedings volume. For the successful local organization of JMLC we thank Muneera Masterson, Ali McNi?e and Fiona Parker and other sta? and student helpers of Oxford BrookesUniversityaswellasRosemaryFrameandJoKnightonandothersta?of JesusCollege,Oxford.TheproceedingsyounowholdwerepublishedbySpringer and we are grateful for their support. Finally, we must thank the many authors who contributed the high-quality papers contained within these proceedings.